Psychological Bullying in Environmental Agency of Central Bengkulu Regency: A Stress-Model Transactional and Coping - Muhammad Eko Oktaviansyah; Olvie Monika Safitri (Da'wa Faculty of Islamic State University Salatiga, 2024)
Workplace psychological bullying remains a significant concern, as the phenomenon in Environmental Agency of Central Bengkulu Regency. Despite Indonesia's low rates of daily workplace stress, 16% of workers report experiencing psychological bullying, negatively impacting mental health and job performance. The tragic case of Dr. Aulia Risma Lestari exemplifies the severe consequences of such bullying, including suicide. The study aims to identify the various forms of psychological bullying encountered by civil servants and the coping strategies they employ. Applying Lazarus and Folkman’s Transactional Model of Stress, this research analyzes how individuals perceive and respond to stressors associated with psychological bullying. A mixed-method approach was used, combining quantitative data from questionnaires completed by 28 civil servants with qualitative insights from comprehensive interviews. The findings reveal that verbal abuse, excessive workloads, neglect, and humiliating pranks are prevalent forms of bullying. The coping strategies employed include problem-focused approaches, such as planful problem-solving and seeking social support, alongside less effective emotion-focused strategies like avoidance. The study underscores the need for robust organizational policies to address psychological bullying and support affected public servants by promoting a more conducive work environment.